The Song of Songs a biography - Pardes, Ilanah 1956- (Lives of great religious books, 2019)
Cover -- Title -- Copyright -- Dedication -- CONTENTS -- ILLUSTRATIONS -- ACKNOWLEDGMENTS -- INTRODUCTION "Draw Me After You, Let Us Run" -- CHAPTER 1 The Rise of Allegory: From Rabbi Akiva to Origen -- CHAPTER 2 Poets and Kabbalists: From Medieval Hebrew Poetry to the Zohar -- CHAPTER 3 Monastic Loves: From Saint Bernard to Santa Teresa -- CHAPTER 4 Modern Scholars and the Quest for the Literal Song: From J. G. Herder to Phyllis Trible -- CHAPTER 5 The Song of America: From Walt Whitman to Toni Morrison -- EPILOGUE "Flee My Lover and Be Like a Deer or Like a Gazelle on the Spice Mountains" -- NOTES -- INDEX.